1978
DOI: 10.1104/pp.62.6.995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of RNA Polymerase from Fremyella diplosiphon

Abstract: We have purified and characterized a DNA-dependent RNA polymerase from the blue-green alga Fremyela dipsiphon. This enzyme, purified by gel filtration, DEAE-ceflulose chromatography, and glycerol gradient centrifugation, is comprised of five polypeptide subunits. Their masses are 161,000, 134,000, 91,000, 72,000, and 41,000 daltons. Preparative electrophoresis of the purified enzyme on nondenaturing gels separates the 41,000-dalton polypeptide from the rest of the enzyme. The enzyme is extremely labile in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1979
1979
1994
1994

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…The rpoCl gene product of N. commune UTEX 584 has an Mr of 71,000, a value which agrees closely with the predicted Mr obtained from sequence analysis (Mr = 70,200). Both of these values are somewhat larger than the values for -y reported in a recent study of 15 taxonomically diverse strains of cyanobacteria (range in Mr, 65,000 to 68,500; 31) and are equivalent to the values reported (Mr = 72,000) for the ry subunits of two other cyanobacteria (10,20).…”
Section: Methodscontrasting
confidence: 50%
See 2 more Smart Citations
“…The rpoCl gene product of N. commune UTEX 584 has an Mr of 71,000, a value which agrees closely with the predicted Mr obtained from sequence analysis (Mr = 70,200). Both of these values are somewhat larger than the values for -y reported in a recent study of 15 taxonomically diverse strains of cyanobacteria (range in Mr, 65,000 to 68,500; 31) and are equivalent to the values reported (Mr = 72,000) for the ry subunits of two other cyanobacteria (10,20).…”
Section: Methodscontrasting
confidence: 50%
“…The remainder of the derived sequence of RpoC2 and the carboxy-terminal region of the E. coli 1' polypeptide showed only minimal correspondence. A comparison of the sizes of the I' subunits in RNA polymerases from diverse strains of cyanobacteria (10,20,31,32) and that derived from our partial sequence analysis of rpoC2 suggests that approximately 650 codons of rpoC2, with unknown function, remain to be analyzed.…”
Section: G E V|kik P E T I N Y R T If Nc I Q G E R T L P N G Q V V|g mentioning
confidence: 99%
See 1 more Smart Citation
“…At the concentrations used in these experiments rif was a specific inhibitor of RNA polymerase in these cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…2). A polypeptide of about the same molecuiar mass had been reported by Miller and Bogorad (1978) in the most highly purified preparation of RNA polymerase from the same strain, and was aiso detected when total extract from Catothrix membranacea was probed with the same two antisera that we used (Schneider and Haseikom, 1988a). Schneider and Haselkorn (1988a) concluded that the 90 kDa poiypeptide could represent a product from proteolysis of the p subunit.…”
Section: Discussionmentioning
confidence: 52%